2014
DOI: 10.1177/1687814020984375
|View full text |Cite
|
Sign up to set email alerts
|

A discretization method for predicting the equivalent elastic parameters of the graded lattice structure

Abstract: In recent years, cellular materials have been widely studied and applied in aerospace and other fields due to the advantages of lightweight and multi-function. However, it is difficult to predict the equivalent elastic properties of the graded lattice structure and other non-uniform cellular materials because of the complex configuration and non-uniformity. A new discretization method for predicting the equivalent elastic parameters of the graded lattice structure is proposed based on the strain energy equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The authors observed a good agreement of the FEN model with the experimental data. Besides the explicit geometric models, the homogenisation approach [12,[15][16][17][18][19] served as a computationally efficient alternative to determine the equivalent effective properties of a heterogeneous lattice. In [17,19], it was coupled with the modified Hill yield criterion and showed good agreement for variable density and surface-based lattices.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a good agreement of the FEN model with the experimental data. Besides the explicit geometric models, the homogenisation approach [12,[15][16][17][18][19] served as a computationally efficient alternative to determine the equivalent effective properties of a heterogeneous lattice. In [17,19], it was coupled with the modified Hill yield criterion and showed good agreement for variable density and surface-based lattices.…”
Section: Introductionmentioning
confidence: 99%